Are Public Relation Strategies Useful for Ghanaian Public Universities: An Exploratory Inquiry on the University of Education, Winneba in Ghana - Kankam, George (Archives of Business Research, 2022)
Universities in the twenty-first century must use successful public relations methods to communicate with both external and internal audiences. Ghana’s public universities are dedicated to change, which necessitates the creation of public relations techniques to increase student enrolment. The exploratory inquiry was used in this study. The consequences of public relations tactics on public relations strategies at Ghanaian public universities are examined in this paper. Based on the existing literature, it is concluded that public universities use a variety of marketing public relations strategies to increase student enrollment, including television advertising, radio advertising and web page information. However, there is still room for improvement, and practical recommendations are made.